Aceh Government Accountability: Implementation of Open Access Data Aceh to Realize Public Transparency a Review of Disclosure Theory - Amirulkamar, Said; Mulya, Sayed Mayzar; Ulfa, Khalida (Formosa Journal of Applied Sciences, 2024)
This research focuses on the implementation of open data Aceh in realizing public transparency through a diclosure theory review. Data sources were obtained through open data Aceh, journals, laws, and online news. The data analysis technique uses Nvivo 12 Plus analysis. The results showed that there were challenges faced in the implementation of open data Aceh and did not rule out the good thing that the Aceh government had also carried out its authority duties in providing transparency to the public. Disclosure Theory is a concept that explains how, why, and to what extent information is disclosed by individuals or organizations. The application of this theory in the context of Open Data Aceh can provide an interesting picture of how the Aceh government manages, discloses, and utilizes data for various purposes for the public, researchers, and others who need this information.